Encouraging Second Language Use in Cooperative Learning Groups - Jacobs, George M; Kimura, Harumi (Beyond Words, 2013)
This article presents, explains and organizes ideas for promoting students’ use of their second language (this term includes foreign language) when they work together in cooperative learning groups. The first part of the article reviews arguments as to whether students of second languages should be encouraged to use their second language with classmates when doing group activities. These arguments are discussed with reference to Second Language Acquisition (SLA) theory. Practical issues are also explored. Next, the majority of the article presents ideas on how to promote second language use during peer interaction. Twenty-nine of these ideas are explained. The ideas are organized into five categories: a role for the L1; understanding the issue; creating a conducive climate; providing language support; and the task. It is recommended that teachers use ideas from the literature on cooperative learning when they ask students to interact.